2022
DOI: 10.3389/fimmu.2022.935114
|View full text |Cite|
|
Sign up to set email alerts
|

Senescence of alveolar epithelial cells impacts initiation and chronic phases of murine fibrosing interstitial lung disease

Abstract: Fibrosing interstitial lung disease (ILD) develops due to the impaired reparative processes following lung tissue damage. Cellular senescence has been reported to contribute to the progression of fibrosis. However, the mechanisms by which these senescent cells initiate and/or drive the progression of lung tissue fibrosis are not yet fully understood. We demonstrated that p21WAF1/CIP1- and p16INK4A-pathway-dependent senescence in type 2 alveolar epithelial cells (AEC2) were both involved in the initiation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…We and others have demonstrated that inhibition of EETs degradation reduces pulmonary fibrosis and COPD in mice [ 46 , 61 ], suggesting the ability of EETs to mitigate chronic age-related lung diseases. More and more studies have confirmed that AEC senescence is the initiating factor of various chronic lung diseases [ 62 , 63 ]. Cell senescence is a complex process that manifests as cell cycle arrest accompanied by changes in SASP gene expression and secretion [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that inhibition of EETs degradation reduces pulmonary fibrosis and COPD in mice [ 46 , 61 ], suggesting the ability of EETs to mitigate chronic age-related lung diseases. More and more studies have confirmed that AEC senescence is the initiating factor of various chronic lung diseases [ 62 , 63 ]. Cell senescence is a complex process that manifests as cell cycle arrest accompanied by changes in SASP gene expression and secretion [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…This exposure may accelerate the growth of preneoplastic cells and subsequently boost the proliferation of cancer cells. Distinct types of proteases identified in the SASP include serine proteases and plasminogen activation pathway regulators, which are both associated with the development of cancer 176,177 . This family consists of the serine proteases, urokinase, and tissue‐type plasminogen activators (uPA and tPA, respectively), the uPA receptor (uPAR), and inhibitors of these serine proteases (PAI‐1 and ‐2) 178 .…”
Section: Morphological Features Of Senescence and Their Role In Tumor...mentioning
confidence: 99%
“…In addition to this, incomplete replication of chromosome ends can lead to telomere shortening (Pineiro-Hermida et al, 2022). Recently, Pineiro-Hermida et al (2022) studied the telomeres of different cell types in the lung by controlling the TRF1 gene and confirmed that fibrosis only occurs when telomeres are disrupted in AECII, and telomere shortening can be compensated by the telomerase reverse transcriptase (TERT) and telomerase RNA component (TERC) (Pineiro-Hermida et al, 2022). Thus, preventing stress-induced telomere damage may prevent cells from entering replicative senescence and fibrosis.…”
Section: Pro-fibrotic Role Of Senescent Aeciimentioning
confidence: 99%
“…However, it has also been demonstrated that TGF-β1 promotes lung fibrosis by inducing apoptosis in AECII. Recent studies have found that in bleomycin-induced lung fibrosis, the early production of TGF-β and platelet derived growth factor subunit A (PDGFA) by senescent AECII may directly promote fibroblast activation and collagen production, which in turn promotes fibrosis ( Yamada et al, 2022 ). In addition to the above signaling pathways, growth factors produced by different neighboring cells, intercellular contacts, immune cells, and the extracellular matrix also regulate the state of AECIIs ( Wu and Song, 2020 ).…”
Section: Senescent Aeciis Promote Idiopathic Pulmonary Fibrosis Devel...mentioning
confidence: 99%